2018
DOI: 10.3892/mmr.2018.8428
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of microRNA-21, -126 and -423-5p alter during clinical improvement and are associated with the prognosis of acute heart failure

Abstract: MicroRNAs are associated with myocardial damage and heart failure (HF). The present study investigated whether the plasma levels of microRNA (miR)‑21, ‑126 and ‑423‑5p alter according to the (de)compensated state of patients with HF and are associated with all‑cause mortality. In 48 patients with HF admitted to the emergency room for an episode of acute decompensation, blood samples were collected to measure miR and B‑type natriuretic peptide levels within 24 h of hospital admission, at the time of hospital di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…In combination with other researchers 'statistics on sample size, we selected more than 60 healthy samples and more than 60 cases of heart failure. Exhaustion samples were analyzed [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. As shown in Figure 1, the aim of the present study was to identify circulating miRNAs in human plasma as biomarkers for the diagnosis of heart failure and its related diseases, to assess the appropriate biomarkers for identifying key characteristics of miRNAs, and to analyze their performance.…”
Section: Introductionmentioning
confidence: 99%
“…In combination with other researchers 'statistics on sample size, we selected more than 60 healthy samples and more than 60 cases of heart failure. Exhaustion samples were analyzed [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. As shown in Figure 1, the aim of the present study was to identify circulating miRNAs in human plasma as biomarkers for the diagnosis of heart failure and its related diseases, to assess the appropriate biomarkers for identifying key characteristics of miRNAs, and to analyze their performance.…”
Section: Introductionmentioning
confidence: 99%
“…Aberrantly expressed miRNAs have been identified by increasing number of studies to be of high potential in the diagnosis and prognosis of CHD patients ( 8 , 9 ). Meanwhile, growing number of studies focusing on the role of miRNA in HF have reported that circulating miRNAs participate in the etiology of HF and are the potential biomarkers in HF patients ( 10 , 11 ). For instance, plasma miR-132 expression is independently associated with disease severity and hospitalization rate of HF patients ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, Zhang et al (10) demonstrated a signi cant correlation of miR-21 with patients' two-year mortality but not with readmission rate. Schneider et al (27) reported that increased level of miR-21 at the time of clinical compensation was associated with better two-year survival and longer rehospitalization-free. Furthermore, they demonstrated that higher miR-423-5p between the time of admission and clinical compensation was associated with fewer hospital readmissions in two-years.…”
Section: Discussionmentioning
confidence: 99%